Rights Offering and Its Effect on Share Price Movement: A Study of Commercial Banks - Pathak, Hari Prasad; Gupta, Sweta (Journal of Nepalese Business Studies, 2018)
This paper examines the effect of rights share issue on share price movement in the banking sector covering the period 2007/08 to 2016/17. In order to find out the share price movement in different selected points of time, pre and post right issue and price relatives were calculated considering the price of 90 days before the right announcement date as the beginning index. Five different points of time were selected to observe the share price movements assuming the announcement date as the reference point of time. Stock price data were obtained from the website of NEPSE. The paper uses correlation coefficient to examine whether the overall market movement has any relationship with the individual share price change. Coefficient of determination is used to identify what proportion of the variation in the share price is explained by the event of right share issue. The result shows that right offering announcements have the signaling effect, but it is negative. The share price of Nepalese commercial banks decreases after the announcement of right in spite of the increase in the market index in the corresponding period. The results highlight the information asymmetry behavior which induces a negative change in share price after the rights announcements. The implication of the result is that investors can anticipate the nature of change in share price after rights issue announcements and develop strategic plans to improve the trading activity.